Analisis Betakaroten, Gula Total, dan Organoleptik Selai Variasi Ubi Ungu (Ipomoea batatas L. Poir) dengan Gula Singkong (Manihot esculenta) : Analisis Betakaroten, Gula Total, dan Organoleptik Selai Variasi Ubi Ungu (Ipomoea Batatas L. Poir) dengan Gula Singkong (Manihot Esculenta) - Handayani, Septy; Hidayati, Khusnul (Amerta Nutrition, 2024)
Background: Purple sweet potato productivity in Indonesia is notably high, particularly in Bondowoso at 213.84 quintals/ha. This variant of sweet potato is rich in beta-carotene, with a content of 4237 µg/100 g, known for its ability to protect cells from free radicals and reduce the risk of diabetes mellitus. Notably, Indonesia ranks third globally in the prevalence of prediabetes, affecting 27.7 million people. In 2022, in Tapen District, Bondowoso, the prevalence of prediabetes, based on Tapen Health Center data, was recorded at 12.36%. Objectives: Analyzing betacarotene, total sugar, and organoleptic propeties of purple sweet potato jam as a prediabetes distraction food. Methods: A quasi-experimental design with a post-test-only control group was employed. The research involved producing purple sweet potato jam with varying ratios of cassava sugar and purple sweet potato (X0: 0% cassava sugar; 100% purple sweet potato; X1: 15% cassava sugar; 85% purple sweet potato; X2: 30% cassava sugar; 70% purple sweet potato; X3: 45% cassava sugar; 55% purple sweet potato). Analysis included determining betacarotene content using the UV-Visible Spectrophotometry method, total sugar using the Luff Schoorl method, and organoleptic evaluation through the hedonic test method. Data were subjected to statistical analysis using the One-Way ANOVA test for betacarotene and total sugar levels, followed by Duncan's post-hoc test. Organoleptic test data were analyzed using the Kruskall Wallis test and Dunn's post-hoc test. Results: The average betacarotene content in treatments X0, X1, X2, and X3 were 4230.3 µg/100 g; 3464 µg/100 g; 2955.6 µg/100 g; and 2257.3 µg/100 g, respectively. Total sugar content averages for treatments X0, X1, X2, and X3 were 2.2%; 13.7%; 27.5%; and 39.2%, respectively. The panelists' preference indicated that sample X3 (45% cassava sugar and 55% purple sweet potato) was the most favored jam. Conclusions: Significant differences were observed in beta-carotene, total sugar, and organoleptic levels of purple sweet potato jam, suggesting that the variation in purple sweet potato and cassava sugar ratios influenced the beta-carotene and total sugar levels in the jam.